KINETICS OF THE GAS-PHASE BROMINATION OF ACTIVATED CARBON: UDC 544.4, 544.723+661.183.2 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
The kinetics of the gas-phase bromination of activated carbon in the temperature range 200–500°C has been studied. It is shown that the bromination of activated carbon with Br2 vapour led to the addition of up to 20–25 wt.% (2.5–3.1 mmol/g) of chemisorbed bromine. The optimal temperature range for the formation of chemisorbed bromine is 300–500°C. The kinetic parameters of the bromination have been found.
Keywords: activated carbon, gas-phase bromination, surface modification